Entry and initial spread of COVID-19 in India: Epidemiological analysis of media surveillance data, India, 2020 - Nuzrath Jahan; Polani Rubeshkumar; Mathan Karuppiah; Irene Sambath; Muthappan Sendhilkumar; Kumaravel Ilangovan; Roopavathi Ongesh; Manikandanesan Sakthivel; Raju Mohankumar; Muthusamy Santhosh kumar; Parasuraman Ganeshkumar; Manickam Ponnaiah; et al. (Elsevier, 2021)
Background: India reported first laboratory-confirmed case of coronavirus disease 2019 (COVID-19) on 30 January from Kerala. Media surveillance is useful to capture unstructured information about outbreaks. We established media surveillance and described the characteristics of the COVID-19 cases, clusters, deaths by time, place, and person during January-March 2020 in India. Methods: The media surveillance team of ICMR-National Institute of Epidemiology abstracted data from public domains of India's Central and State health ministries, online news and social media platforms for the period of January 31 to March 26, 2020. We collected data on person (socio-demographics, circumstances of travel/contact, clinical and laboratory), time (date/period of reported exposures; laboratory confirmation and death) and place (location). We drew epidemic curve, described frequencies of cases by age and gender. We described available details for identified clusters. Results: As of March 26, 2020, India reported 694 (Foreigners = 45, 6%) confirmed COVID-19 cases (Attack rate = 0.5 per million population) and 17 deaths (Fatality = 2.5%) from 21 States and 6 Union Territories. The cases were higher among 20-59 years of age (60 of 85) and male gender (65 of 107). Median age at death was 68 years (Range: 38-85 years). We identified 13 clusters with a total of 63 cases and four deaths among the first 200 cases. Conclusion: Surveillance of media sources was useful in characterizing the epidemic in the early phase. Hence, media surveillance should be integrated in the routine surveillance systems to map the events specially in context of new disease outbreaks.